Investigation into the use of carbon nanofilaments in bone repair applications - Walter, Daniel Mark (2007)
The potential of carbon nanofilaments for use in surface modification of implants and as fillers in biocompatible polymer composites was investigated with particular respect to nanofilament size and structure. Carbon nanofilaments were synthesised using chemical vapour deposition or obtained commercially, which provided a range of carbon nanofilament average diameters (13 nm, 134 nm, 142 nm, 155 nm) and structures (platelet, platelet and herringbone, multi-walled nanotubes and vapour-grown nanofibres).